PENGARUH MODEL PEMBELAJARAN PAIRED STORY TELLING BERBANTUAN BONEKA TANGAN TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS III SD NEGERI 1 MONTONG BELAE KECAMATAN KERUAK - Gea Desta Rini; AriF Rahman Hakim; Yuniar Lestarini; Zalia Muspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of the Paired Storytelling learning model assisted by hand puppets on Indonesian language learning outcomes of third-grade students at Montong Belae 1 Elementary School. The background of the study is the low speaking skills and learning outcomes of students due to the dominance of the lecture method. The study used a quantitative approach with a One Group Pretest-Posttest design on 24 students. Data were collected through observation and multiple-choice tests that were tested for validity and reliability. The results showed an increase in the average score from 30.75 (pre-test) to 53.875 (post-test), with a difference of 23.125 points. The t-test yielded p < 0.01, indicating a significant effect. In addition to improving cognitive learning outcomes, this model also fosters student engagement, speaking skills, and self- confidence. Thus, paired story telling using hand puppets is effective in improving Indonesian language learning outcomes in elementary schools.